Graft pathology at the time of harvest: impact on long-term survival - Yuan,Shi-Min (2014)
Objective: This study aims to present the graft pathology at the time of harvest and its impact on long-term survival. Methods: The remnants of the bypass grafts from 66 consecutive patients with coronary artery disease receiving a coronary artery bypass grafting were investigated pathologically, and pertinent predictive risk factors and survival were analyzed. Results: Medial degenerative changes with or without intimal proliferation were present in 36.8%, 37.8% and 35.6% of left internal mammary artery (IMA), radial artery and saphenous vein grafts. There were 2 (3.0%) hospital deaths and 9 (14.1%) late deaths. Multinomial logistic regression revealed left IMA pathological changes, dyslipidemia, history of percutaneous transluminal coronary angioplasty/stent deployment and Y-graft were significant predictive risk factors negatively influencing the patients’ long-term survival. Kaplan-Meier survival analysis revealed that the long-term survival of patients with left IMA pathological changes were significantly reduced compared with those without (74.1% vs. 91.4%, P=0.002); whereas no differences were noted in long-term survivals between patients with and without pathological changes of the radial arterial or saphenous vein grafts. Conclusion: Pathological changes may be seen in the bypass graft at the time of harvest. The subtle ultrastructural modifications and the expressions of vascular tone regulators might be responsible for late graft patency. The pathological changes of the left IMA at the time of harvest rather than those of the radial artery or saphenous vein graft affect significantly longterm survival. Non-traumatic maneuver of left IMA harvest, well-controlled dyslipidemia and avoidance of using composite grafts can be helpful in maintaining the architecture of the grafts.